2013
DOI: 10.1111/jvim.12236
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically Visualized Lesions, Histologic Findings, and Bacterial Invasion in the Gastrointestinal Mucosa of Dogs with Acute Hemorrhagic Diarrhea Syndrome

Abstract: BackgroundEtiology of hemorrhagic gastroenteritis (HGE) syndrome in dogs is unknown and histopathologic and microbial investigations have only been performed post mortem.ObjectiveTo identify characteristic intra vitam endoscopic and histologic mucosal lesions, as well as bacterial species, within the mucosa of dogs with HGE.AnimalsTen dogs diagnosed with HGE were included. Eleven dogs with gastroduodenoscopy and different intestinal diseases were used as controls for microbial changes. Dogs pretreated with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 38 publications
6
93
1
2
Order By: Relevance
“…If emesis occurs, this is not due to gastritis since a recent study showed that mucosal lesions associated with AHDS are restricted to the intestines (Unterer and others 2014). As haemorrhagic diarrhoea might not be apparent until as much as 52 hours after onset of vomiting, it is important to keep in mind that AHDS is a possible differential diagnosis for haematemesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If emesis occurs, this is not due to gastritis since a recent study showed that mucosal lesions associated with AHDS are restricted to the intestines (Unterer and others 2014). As haemorrhagic diarrhoea might not be apparent until as much as 52 hours after onset of vomiting, it is important to keep in mind that AHDS is a possible differential diagnosis for haematemesis.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, acute haemorrhagic enteritis caused by certain enterotoxigenic strains of Escherichia coli has a very similar clinical presentation (Triolo and Lappin 2003). In dogs, different aetiologies have been discussed, including intestinal type 1 hypersensitivity reaction to food components or bacterial endotoxin, and enterotoxigenic clostridial strains (Cave and others 2002, Triolo and Lappin 2003, Hall and German 2010, Unterer and others 2011, 2014). A rapid clinical improvement is typically seen with symptomatic therapy—aggressive fluid therapy being the mainstay of treatment (Triolo and Lappin 2003, Unterer and Hartmann 2009, Unterer and others 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This syndrome had previously been named canine ‘haemorrhagic gastroenteritis’ (Burrows 1977) and is characterised by acute onset of haemorrhagic diarrhoea, commonly accompanied by a marked haemoconcentration (Burrows 1977, Mortier and others 2015). Although the exact aetiology has not yet been fully revealed, there is evidence that Clostridium perfringens is involved in the pathogenesis of AHDS (Unterer and others 2014). Quantitative PCR showed a significant increase of C perfringens in the faeces of dogs with AHDS compared with healthy dogs.…”
mentioning
confidence: 99%
“…Na clínica de animais de companhia é alta a frequência de cães com síndrome da diarreia hemorrágica aguda, e geralmente essa cursa com uma elevada taxa de mortalidade, por evoluir para quadros de sepse (Unterer et al, 2014).…”
Section: Introductionunclassified